Studi Neraca Air Di Pulau Rupat - Kristin, Vyronika; Rinaldi, Rinaldi; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Rupat Island is one of the island that surrounded by oceans and the unavaiability of water supply company cause the people of the island to rely on rain water to get clean water. Population growth, land use change, the behavior of hydrology and building infrastructure water inadequate affect the water availability relatively constant, which in the end feared will cause imbalance between the needs and availability. So, we need a study of water balance with the aim to analyze the needs, availability and water balance at Rupat Island. Analysis of the availability of water is conducted by rainfall data of half monthly period from 2006 to 2015 using National Rural Electric Cooperative Association (NRECA) and F.J. Mock with discharge comparison is from Automatic Water Level Recorder (AWLR) Pantai Cermin for calibration. From this calibration will be compared with finding the Root Mean Square Error (RMSE) value and obtained the better method is NRECA. The needs was calculated until 2035 with assuming all grades needs except domestic demand that is considered a constant. Analysis of water balance is based on the probability of 80%, 20% and average discharge from availability. The final result of this research showed that availability for Qinflow 80% condition going on deficit for particular months. However, for the others conditions going on excess water throughout the year and it will still be able to fulfill the needs of water until 2035 with assuming no significant changes of catchment area.Keywords: Water Balance, NRECA, F.J. Mock.